Comparison of blood transfusion and surgical complications in peripartum hysterectomy when anticipated and unanticipated. (2nd January 2016) - Maher, N.; Gleeson, N.; Darcy, T.; Byrne, B.
Abstract : The aim of the study was to determine the incidence and aetiology of peripartum hysterectomy (PH) for major obstetric haemorrhage (MOH) in our population and to compare estimated blood loss (EBL), blood transfusion, surgical complications and duration of hospital stay in PH that was anticipated and PH that was unanticipated. 26 cases of MOH requiring PH were identified from 50, 548 women who delivered between 1 January 2006 and 31 December 2011 (0.5/1000). PH was anticipated in 17 and unanticipated in 9 cases. When compared, the anticipated group was more likely to have placenta accreta 15/17 (88%) vs 4/9 (44%): p = 0.03 and a gynaecological oncologist as the principal operator 15/17 (88%) vs 3/9 (33%): p = 0.007. The EBL 5.5 ± 3.7 SD vs 6.6 ± 3.9 SD l; p = 0.5, units of red cell concentrate or RCC transfused 7 ± 5 SD vs 9 ± 5 SD: p = 0.3, and mean operating time 134 ± 60 SD vs 190 ± 96 SD min: p = 0.07 were less in the anticipated than the unanticipated group, but not significantly so. The intraoperative complication rate 7/17 (41%) vs 3/9 (33%): p = 1.0 and the mean duration of hospital stay 7 ± 1 SD vs 8 ± 3 SD days: p = 0.27 were similar in both groups. PH is associated with a large volume of blood loss and significant surgical complications regardless of whether the procedure is anticipated or not.